Sustainable food procurement in British and Irish zoos. Issue 10 (30th September 2014) - Hanson, Jonathan; Holt, Diane
Abstract : Purpose: – The purpose of this paper is to assess the sustainable food procurement (SFP) of members of the British and Irish Association of Zoos and Aquariums (BIAZA). It also considered the inconsistencies between their animal and human food supply chains, as well as between their procurement priorities and practices. Design/methodology/approach: – A quantitative, cross-sectional approach was employed, involving the use of a web-based questionnaire to gather data from 41 BIAZA members across 21 indicators of food sustainability. The results were considered within a sustainable supply chain management (SSCM) framework. Findings: – There was considerable variation amongst the issues considered by zoos during the SFP process for their animal and human food operations. For both, local expenditure, nutritional content and packaging reduction were some of the highest scoring indicators in practice and as priorities. The overall levels of SFP were found to be equal between the human and animal food supply chains. Significantly low levels of inconsistency were found between the two, practically and in terms of procurement aspirations. Within both supply chains, there was also very few significant gaps between procurement priorities and actions. Originality/value: – The originality of this study lies in its comparison of procurement practices and priorities for two contemporaneous but distinct food supply chains. It demonstrates that it is possible to have a high overall degree of consistency between two parallel, but contrasting, supply chains, as well as between procurement priorities and priorities. It will be of use in SSCM, particularly within values-led organisations.